Desain Pengering Makanan dan Analisis Neraca Massa Pada Pembuatan Tepung Sawi - Erwan Adi Saputro; Mutasim Billah; Ardika Nurmawati; AR Yelvia Sunarti; Elene Afrisia Efendi (JSSIT: Jurnal Sains dan Sains Terapan, 2025)
The majority of the residents of Giripurno Village rely on activities in the agricultural and plantation sectors. One of the plantation commodities with high prospects in the area is mustard greens. Until now, the harvested mustard greens from local plantations have generally been marketed in fresh form without undergoing any processing. However, this commodity has the potential to generate various processed products with higher economic value if handled appropriately. One form of processing that can be carried out is converting mustard greens into flour. Therefore, this study focuses on the design of a simple drying device (food dehydrator) and the mass balance analysis in the mustard flour production process. This research was conducted using literature review, the design of a box-type insulated dryer equipped with incandescent lamp heating elements and a temperature control system, and the mass balance analysis of mustard flour production. Based on the analysis of the first experiment, 12 grams of mustard flour were obtained from 150 grams of fresh mustard greens. In the second experiment, 15 grams of mustard flour were obtained from 175 grams of fresh mustard greens.